Nanosensors for determining the presence of bacteria - Goluch, Edgar (Henry Stewart Talks, 2015)
Abilities of bacteria to organize and adapt in dynamic situations, Electrochemical sensors for bacterial analysis and real-time infection detection, Micro/nano-fluidic devices to trap and isolate individual bacterial species